How digital marketing platforms are contributing to the small and entrepreneurs' businesses - in Bangladesh E-Commerce Industry - Monika, Romana Yasmin (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.